Antiplatelet aggregation and endothelial protection of I4, a new synthetic anti-diabetes sulfonylurea compound. (June 2015) - Ma, Lingman; Lu, Na; Wu, Guanzhong
Abstract I4 is a new synthetic anti-diabetes sulfonylurea compound. The aim of present study was to investigate the preventive effects and primary action mechanisms of I4 on platelet-mediated arterial thrombosis. Platelet aggregation and 5-hydroxytryptamine (5-HT) secretion ex vivo was detected. The time-to-occlusion (TTO), thrombus weight and content of von Willebrand factor (vWF) in rat model of electrical- and ferric chloride-induced vessel occlusion were determined. Meanwhile, a rat model of type 2 diabetes mellitus (T2DM) was established to evaluate the effect of I4 on levels of plasma p-selectin, 6-keto-prostaglandin F1a (6-keto-PGF1a), thromboxane B2 (TXB2), tissue-type plasminogen activator (t-PA) and type-1 plasminogen activator inhibitor (PAI-1). NO synthesis, NOS activity, adhesion of platelet toward endothelial cell and intercellular adhesion molecule-1 (ICAM-1) expression were examined. Results showed that I4 exhibited a higher inhibitory potency than Glimepiride on ADP-induced platelet aggregation and 5-HT release ex vivo. In addition, I4 reduced the thrombus weight and content of vWF and markedly prolonged TTO. Oral administration of I4 (1 ∼ 10 mg/kg) inhibited p-selectin production, elevated the ratio of plasma 6-keto-PGF1a/TXB2 and t-PA/PAI-1 in T2DM rats. Furthermore, I4 significantly improved NO synthesis and NOS activity, lowered adhesion ratio of platelet toward endothelial cells and ICAM-1 expression on HUVECs. These observations suggest that I4 markedly improves platelet-mediated arterial thrombosis by inhibiting platelet activation and release reaction, ameliorating the endothelial dysfunction such as the suppression of vWF production and the reduction of the overexpression of ICAM-1, displayed its potential in alleviating diabetes-associated vascular complications.